Frequency of CYP2D6 Alleles Including Structural Variants in the United States - Del Tredici, Andria L.; Malhotra, Alka; Dedek, Matthew; Espin, Frank; Roach, Dan; Zhu, Guang-dan; Voland, Joseph; Moreno, Tanya A. (Frontiers in Pharmacology, 2018)
The CYP2D6 gene encodes an enzyme important in the metabolism of many commonly used medications. Variation in CYP2D6 is associated with inter-individual differences in medication response, and genetic testing is used to optimize medication therapy. This report describes a retrospective study of CYP2D6 allele frequencies in a large population of 104,509 de-identified patient samples across all regions of the United States (US). Thirty-seven unique CYP2D6 alleles including structural variants were identified. A majority of these alleles had frequencies which matched published frequency data from smaller studies, while eight had no previously published frequencies. Importantly, CYP2D6 structural variants were observed in 13.1% of individuals and accounted for 7% of the total variants observed. The majority of structural variants detected (73%) were decreased-function or no-function alleles. As such, structural variants were found in approximately one-third (30%) of CYP2D6 poor metabolizers in this study. This is the first CYP2D6 study to evaluate, with a consistent methodology, both structural variants and single copy alleles in a large US population, and the results suggest that structural variants have a substantial impact on CYP2D6 function.